Microfluidic diffraction phase microscopy for high-throughput, artifact-free quantitative phase imaging and identification of waterborne parasites. (December 2019) - Gu, Xin; Lei, Lei; Sun, Yunfei; Si, Xiongyuan; Wang, Mingdi; Li, Feng; Yang, Gang; Yang, Limei; Pan, Gebo; Huang, Wei
Highlights: A MFDPM for high-throughput quantitative phase imaging of waterborne parasites is developed. Pronounced artifacts in phase maps are eliminated by tuning refractive index of immersion medium. Waterborne (oo)cysts can be identified accurately using PCA and LDA algorithms. MFDPM is of great value to label-free detection of waterborne microorganisms and cells. Abstract: An artifact-free microfluidic diffraction phase microscopy (MFDPM) system to measure quantitative phase maps of individual Giardia lamblia ( G. lamblia ) cysts and Cryptosporidium parvum ( C. parvum ) oocysts is developed. The system includes a diffraction phase imaging unit aligned with a polydimethylsiloxane (PDMS) microfluidic chip. The microfluidic chip consists of arrays of U-shaped hydrodynamic trapping structures used to trap single cysts/oocysts, and a micromixer to precisely adjust the refractive index of immersion medium in the microfluidic chamber. When the refractive index of immersion medium is tuned to be equal to that of PDMS, the pronounced artifacts in quantitative phase imaging (QPI) originating from diffraction and scattering at the edges of trapping structures can be eliminated. The artifact-free quantitative phase maps of single microparticles are retrieved using Goldstein's algorithm. Principal component analysis (PCA) is implemented to extract the distinctive features of the quantitative phase maps of G. lamblia cysts and C. parvum oocysts, and they can be identified with 100% accuracy using linear discriminant analysis (LDA) algorithm. The MFDPM is demonstrated to be a simple, accurate and high-throughput technique for artifact-free quantitative phase imaging of waterborne protozoa, and has great potential for label-free and rapid detection and identification of waterborne microorganisms.